2021
DOI: 10.1371/journal.pone.0256138
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the distribution of African swine fever virus within a feed mill environment following manufacture of inoculated feed

Abstract: It is critical to understand the role feed manufacturing may have regarding potential African swine fever virus (ASFV) transmission, especially given the evidence that feed and/or ingredients may be potential vectors. The objective of the study was to evaluate the distribution of ASFV in a feed mill following manufacture of contaminated feed. To accomplish this, a pilot-scale feed mill consisting of a mixer, bucket elevator, and spouting was constructed in a BSL-3Ag facility. First, a batch of ASFV-free feed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Additionally, these data are in agreement with risk assessments put When focusing on environmental samples collected at the feed mill in the current investigation, there were only nine of 1159 samples which contained detectable ASFV DNA (0.78%). Data recently published indicate that when using feed manufacturing equipment in a controlled research setting to mix feed inoculated with ASFV, the virus can be found on a number of different surface types even after multiple subsequent batches of feed are mixed (Elijah et al, 2021) In the current investigation, several key areas of environmental contamination were identified including high-traffic areas and worker clothing. Likewise, the greatest area for contamination within the live animal transfer infrastructure sampled was live animal transport vehicles, specifically the cabs of these vehicles.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Additionally, these data are in agreement with risk assessments put When focusing on environmental samples collected at the feed mill in the current investigation, there were only nine of 1159 samples which contained detectable ASFV DNA (0.78%). Data recently published indicate that when using feed manufacturing equipment in a controlled research setting to mix feed inoculated with ASFV, the virus can be found on a number of different surface types even after multiple subsequent batches of feed are mixed (Elijah et al, 2021) In the current investigation, several key areas of environmental contamination were identified including high-traffic areas and worker clothing. Likewise, the greatest area for contamination within the live animal transfer infrastructure sampled was live animal transport vehicles, specifically the cabs of these vehicles.…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, the ability to detect viral RNA within the environment can persist for extended periods of time, and can only be removed through intensive cleaning, disinfection, and thermal processing measures (Huss et al., 2017 ). Recently, evidence has been generated that indicates ASFV can become widely distributed within a feed mill when manufacturing inoculated feed in a controlled setting (Elijah et al., 2021 ). Additional research is necessary to further understand these environmental distribution characteristics in a real‐world setting, but initial evidence indicates that environmental sampling for ASFV within a feed manufacturing facility may be a useful diagnostic tool similar to sampling for PEDV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental sampling using 10 × 10 cm cotton gauze was conducted similar to Elijah et al ( 12 ). Briefly, environmental swabs were taken after the isolation nursery was sanitized but before new pigs were placed at the location.…”
Section: Methodsmentioning
confidence: 99%
“…Environmental sampling using 10 × 10 cm cotton gauze was conducted similar to Elijah et al (12). Briefly, environmental FIGURE Depiction of the relationship between the isolation nursery barn, the farrow-to-finish site, and o -site finisher barn and timeline of events during this investigation of atypical porcine pestivirus persistence (APPV) in pigs.…”
Section: Environmental Samplingmentioning
confidence: 99%